If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(y + -2) + 15 = -5(y + -7) + -10 Reorder the terms: 3(-2 + y) + 15 = -5(y + -7) + -10 (-2 * 3 + y * 3) + 15 = -5(y + -7) + -10 (-6 + 3y) + 15 = -5(y + -7) + -10 Reorder the terms: -6 + 15 + 3y = -5(y + -7) + -10 Combine like terms: -6 + 15 = 9 9 + 3y = -5(y + -7) + -10 Reorder the terms: 9 + 3y = -5(-7 + y) + -10 9 + 3y = (-7 * -5 + y * -5) + -10 9 + 3y = (35 + -5y) + -10 Reorder the terms: 9 + 3y = 35 + -10 + -5y Combine like terms: 35 + -10 = 25 9 + 3y = 25 + -5y Solving 9 + 3y = 25 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. 9 + 3y + 5y = 25 + -5y + 5y Combine like terms: 3y + 5y = 8y 9 + 8y = 25 + -5y + 5y Combine like terms: -5y + 5y = 0 9 + 8y = 25 + 0 9 + 8y = 25 Add '-9' to each side of the equation. 9 + -9 + 8y = 25 + -9 Combine like terms: 9 + -9 = 0 0 + 8y = 25 + -9 8y = 25 + -9 Combine like terms: 25 + -9 = 16 8y = 16 Divide each side by '8'. y = 2 Simplifying y = 2
| y^2=-4y-10 | | 5n+6-3n=3.7 | | 4x+3y+6z=2825 | | 72=6x+4(x-12) | | 4k+h=-2k-144 | | 4x-134+18=4x-32 | | x(x-6)= | | 6(6x-6)+6=8x-8 | | 3j+4=19 | | 7x+8-22=44-7x | | 2x^2+6x-5=85+x^2+1 | | 30(198x-178)-7921=0 | | Y+18=5y-10 | | 4+2r=10 | | 3(y-2)+15=-5(q-7)-10 | | 115=2x+7(4x-5) | | -8w-14=34 | | 4+2g=8 | | b+(-42)=(-86) | | y^2-4y-x^2+4=0 | | 15(198x-178)-7921=0 | | 4x-5=-4+6+6x-1 | | 2(12b+7)+9b-1=180-9b-1 | | Y+20=4y-15 | | -2x+12+3x=2+x+10 | | 5-7(2-x)=31-4(x-5) | | 6(x-2)-(x+2)=3x-18 | | 5(x+5)-20=0 | | 123=5x+6(2x-5) | | -2(x-2)-4x=3(x+10)-9x | | 5x-8c=-6 | | -20=8x+2x |